LAW ENFORCEMENT AGAINST THE CRIME OF THEFT WITH VIOLENCE CAUSING DEATH (STUDY ON LALAT POLICE) - Sihotang, Sihar Maruli Tua; Zulyadi, Rizkan; Frensh, Wenggedes (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze law enforcement by the Langkat Police Resort (Polres) regarding the crime of theft with violence resulting in death. The research questions include: (1) what form of law enforcement is carried out by the Langkat Police Resort (Polres) regarding the crime of theft with violence resulting in death; (2) what factors hinder the law enforcement process; and (3) what efforts are made by the Langkat Police Resort (Polres) in overcoming the crime of theft with violence resulting in death. This study uses an empirical legal research methodology, namely research that positions law as a social phenomenon that can be observed through the behavior of law enforcement officers and community responses. The type of research used is field research, collecting primary data through in-depth interviews with investigators, Criminal Investigation Officers (NCOs), and relevant officials at the Langkat Police Resort, as well as secondary data in the form of laws and regulations and legal literature. The research is descriptive and analytical in nature, namely describing empirical facts regarding the law enforcement process and then analyzing them based on relevant legal theories and provisions.